Evaluation of Respiratory Health among Refuse Management and Sanitation Board Workers in Kano Metropolis - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Kano State Refuse Management and Sanitation board workers are constantly exposed to bioaerosol inhalation, including toxins and biotoxins that are been released from the waste.Aims:The aim of this study is to evaluate and determine the respiratory health status of Workers.Methodology:The study was a cross-sectional survey with 129 participants recruited using a convenience sampling technique. Forced vital capacity, forced expiratory volume in 1 s and St. George questionnaire were used to collect data and the result was analysed using descriptive statistics of frequencies, percentages and graphs, while the differences and relationships were obtained using one-way ANOVA and Spearman rank correlation co-efficient, respectively.Results:The mean age of the participants was 34.2 years. Up to 75.2% of the participants were male, whereas 24.8% were female. Up to 40% of participants did not have any respiratory symptoms, 35% had mild symptoms, 14% had moderate symptoms and 11% had severe respiratory symptoms. The symptoms include dyspnea, coughing, excessive mucus secretion and breathlessness. Respiratory symptoms was positively related to the length of exposure (P= 0.029). There was no significant difference in respiratory symptoms between waste collectors, sweepers and drivers. Furthermore, no relationship was found between the age of the workers and respiratory symptom (P= 0.056). Significant difference (P= 0.003) was observed between gender of the participants and respiratory health.Conclusions:Waste disposal work has significant impact on respiratory health. The provision of health education for safety and proper use of personal protection is necessary to reduce the impact of pollutant on respiratory health.